Cooperative learning and pupils' achievement in geography, history and civics - Neri, Marichelle Fillarca (2005)
A pretest-posttest control group design was used in investigating the relative effectiveness of the Cooperative Learning Approach employing Student-Team Achievement Division, JIGSAW II and Team-Games Tournament strategies on academic achievement in Heograpiya, Kasaysayan 6 of Sto Nino Elementary School, Marikina City. Results revealed that pupils taught using Cooperative Learning Approach gained significantly more knowledge in HKS 6 than the pupils taught in the conventional teaching method. The three cooperative learning approaches utilized in the study were useful in promoting academic achievement, enhancing self-esteem, and in developing positive relationship and social support
"April 2005."
Thesis (M.A. Education : Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Elementary) -- Philippines -- Marikina City; Group work in education -- Philippines -- Marikina City